ANALYSIS OF HEALTH WORKERS' PRACTICE NEGLIGENCE: REVIEW OF ETHICAL CODES AND LEGAL ASPECTS - Qomariah, Siti Nur; Revani, Hilda Dea (SYNTIFIC, 2025)
Background. Healthcare professionals hold a unique ethical and legal responsibility for patient health, where negligence is considered a failure to maintain professional standards that can result in patient harm, leading to both ethical concerns and legal consequences. This study aimed to analyze health workers’ practice negligence to clarify ethical codes and legal concepts. Research method. This approach emphasizes review articles and normative studies, viewing law as a collection of written norms found in legislation, jurisprudence, and expert opinions. The study aims to conduct a normative analysis of the current, formally applicable legal framework, utilizing a statutory method to examine Law Number 17 of 2023, Law Number 29 of 2004, additional regulations from the Criminal Code, and relevant sectoral laws. Findings. The relationship between ethical norms and legal obligations in medical practice illustrates that ethical standards often precede legal frameworks by establishing professional expectations. Legal rules serve to enforce minimum care standards, protecting patients and practitioners. Negligence constitutes a breach of duty leading to harm, making health professionals liable under civil law for unlawful acts causing injury, thereby allowing patients to seek compensation. In Indonesia, health law defines legal obligations and penalties for negligence, with civil and criminal liabilities relevant in severe injury or death cases. Conclusion. The importance of clarity in legal standards to adjudicate malpractice claims. A key harmonization, when ethical and legal systems diverge, conflicts can arise, for instance, between respecting autonomy and mandated interventions. Ethical guidelines can help resolve these tensions, but cannot substitute for legal accountability.